Faktor yang Mempengaruhi Hubungan Sosial Peserta Didik di SMP Negeri 10 Padang - Z, Fera Ardanti (Bimbingan dan Konseling, 2014)
This research staris at the unhormany social relationship among the students. Its purpose is to describe the factors which in influence the students social relationship in SMP Negeri 10 Padang, with the limited problem are 1) internal factor which influence the students social relationship and, 2) external which influence the students social relationship. This research is a kind of quantitative descriptive. Research population sample is the entire of SMP Negeri 10 Padang students that those are 810 students. The sampling used is simple random sampling that takes 100 students. The instrument of the research uses questionaite. Furthemore, for data analysis the research using presentage technique. The result of the research tells that generally the factors which influence students social relationship is plural criterion. The research result relies on sub variabel, that are 1) internal factor which influences students social relationship is on plural criterion, 2) external factor which influences students social relationship is on plural criterion as well. In conclusion more factors which influence students social relationship so that better social relationship among students will develop.